New optical nova in M 31 - Henze, M.; Pietsch, W.; Burwitz, V.; Hatzidimitriou, D.; Reig, P.; Primak, N.; Papamastorakis, G. (2008)
We report the discovery of a new nova in M 31 on four consecutive dithered stacked R filter CCD images, obtained on 2008 Oct 18.91, with the 1.3m Ritchey Chretien f/7.5 telescope at Skinakas Observatory, Crete, Greece, using an Andor DZ436-BV CCD Camera (with a Marconi 2k x 2k chip with 13.5µm sq. pixels). The R magnitude of the object was 18.3. The object is already visible on several earlier R images obtained with the same telescope and camera.
Keywords: Novae; Optical